The Attitude of Hemodialysis Units Nurses on Factors Reducing Job Fatigue - Burneikaitė, Guoda; Spirgienė, Lina (Slauga. Mokslas ir praktika, 2023)
The aim is to find out the factors that can reduce fatigue at work, from the point of view of hemodialysis unit nurses. Methods. The study was conducted in 2021. December - May 2022 in six hemodialysis departments, clinics, and centers. 21 nurses participated in the study. A qualitative analysis of the research was performed. Bioethics approval from the Lithuanian University of Health Sciences was obtained for the study (protocol No. BEC – SL(M)-131). Results. In the opinion of nurses who work in hemodialysis units, a lower workload, namely a lower amount available per nurse, would reduce their fatigue. Experienced physical fatigue at work would be helped by fewer opportunities for important physical activities and/or physiotherapy, psychological fatigue would be helped by reducing the opportunity to also attend physical activities, a free sports club, or yoga. One of the most important factors determining work motivation and satisfaction is salary. Conclusions. Flexible work schedules and optimal workload, sufficient salary, and the possibility of offering employees physical or other relaxing activities organized by a physiotherapist are important factors in reducing the fatigue of hemodialysis unit nurses at work.